Experimental investigations on novel double-sleeve tubebolt moment connection to concrete filled tubular column / Mahdi Zeinizadeh Jeddi - Mahdi Zeinizadeh, Jeddi (2017)
Concrete-filled tubular (CFT) columns have been commonly used as part of special moment-resisting frames in high-rise buildings for decades. Blind-bolts mechanical systems are widely adopted for on-site bolting of open beam to tubular column connections. The common types of blind bolts are Hollo-Bolt (HB) and its modified version, Extended Hollo Bolt (EHB). However, EHB bolts could not provide sufficient moment-resistance capacity and exhibited several shortcomings such as bolt slippage, low load transfer mechanism, bolt elongation and column face bending. A new blind bolt called Double sleeve-TubeBolt was proposed in this research to solve the above mentioned problems. The first part of this research was experimental pull-out tests of individual bolt under monotonic loading to obtain the performance of the TubeBolt and EHB bolt. The force-displacement, anchorage and elongation behavior of the bolts were determined. The test specimens were varied according to type of bolts, bolt diameter, concrete confinement and column wall thickness. For the second part of this study, six half scale cruciform specimens, connecting an open beam to CFT column with the novel blind bolt connection were tested under cyclic loading to investigate the seismic performance of the connections. The effects of different parameters on the behavior of the connection, such as bolt type, bolt grade and stiffeners at the top and bottom of the endplate were investigated. The failure modes, hysteretic performance, rotation capacity, strength and stiffness degradation, ductility and energy dissipation of the connections were analyzed. The pull-out test results indicate that the tensile capacity of the TubeBolt is 2.5 times higher than the existing EHB bolt. In addition, the Tubebolt has better anchorage and the elongation has reduced to 68% compared to the existing EHB bolt. The cyclic test results of the cruciform specimens demonstrate that the new blind bolted connections exhibit a large hysteretic enclosed area, good ductility, and excellent energy dissipation compared to the EHB connection. The TubeBolt has achieved better performance compared to the EHB bolt, with 36% and 24% increase in the maximum strength and initial stiffness, respectively. No column face deformation and concrete damage is observed in the test. The results prove that the proposed TubeBolt connection satisfies the seismic provisions and ductility design requirements to be utilized in moment-resisting frames in seismic zones.